As contradições do cooperativismo na educação: um estudo de caso na Cooperativa de Ensino de Rio Verde – GO (COOPEN) entre os anos 2011 e 2015 - Borges, Marcelo Augusto de Lacerda (2017)
The Educational Cooperative of Rio Verde City – GO (COOPEN) was collated in this work between the years of 2011 and 2015 with the goal to unveil its institutional contradictions, taking into account that there were paradoxes between the cooperative principles/values defended by the school in comparison to the concreteness of its educational practice focused on the execution of the Market privatistic logic. This indicative summary clarifies that – through the methodological bias of historical and dialectical materialism – the notion of "contradiction" used here sought to demonstrate the incongruity between what was formally proclaimed by the teaching cooperative (its appearance) and what became properly effective as its educational practice (its essence).Within this objective of revealing its institutional antinomies, a "case study" on COOPEN was carried out, using a qualitative analytical perspective supported by documentary research and semi-structured interviews. The documentary research resorted to the basic references that defined the institution's history and functioning, such as its social statutes, its school regulations, the minutes of an ordinary assembly meeting, and the statistical data concerning the teaching cooperative. The interviews were carried out with three segments of the cooperative, that is: the cooperative members, the teachers and the students of the institution. The discursive analyzes of the interviews allowed the formation of a set of assertive thematic units on the cooperative, which were used so as to point out the contradictions of this cooperative school. For such, in search of its seminal contradictions, it was necessary to retake, as bibliographical research, the sociogenesis of the cooperative movement as a historical form of production/management.In the nineteenth century, workers' cooperative associations provoked theoretical clashes around themselves, splitting those who regarded as credible their revolutionary potentialities of overcoming the bourgeois order – even if incipient – from those who placed in its fulfillment a reformist and integrative character in relation to the capitalist productive logic. At the end of the 20th century and the beginning of the 21st century, the debate was updated because: the socialist experiences of the Soviet model succumbed, the perversity of the mercantile mode governed by capital endured and, in the series of events, the institutionality crisis of the Fordist wage model brought the weakening of trade union organizations, the dismantling of social and labor rights, the precariousness of forms of work, the increase in unemployment rates and the resumption of cooperative experiences as a singular effect of these transformations. In this historical framework of reconfiguration of the world of work, framed by the logic of productive restructuring, the thesis sought to point out the contradictions of cooperativism in education as a participant in this social totality. It was understood in this case study that the cooperative management in COOPEN was driven by a remarkable character of ideologization – in the Marxian/Engelsian sense of the conceptual notion of ideology. Therefore, the work aimed at revealing that in its effective reality, the ideals of cooperativism were not fulfilled as they were claimed by the teaching cooperative, causing a distance to appear between what was ideally proposed by the school and its effective reality as an educational institution.